Wolność gospodarcza a poczucie odpowiedzialności za dobro wspólne - Walczak-Duraj, Danuta (Annales. Etyka w Życiu Gospodarczym, 2014)
The main purpose of the paper is to describe, diagnose and interpret mutual rela-tions between the idea of economic freedom and the sense of responsibility for the common good in modern societies functioning in the system of a free market economy. The starting point for the analysis is a reference to predominating scientific discourses and their appearance in the public sphere. These discourses also take up the problem of mutual relations between freedom and responsibility, including responsibility for the common good. One specific case of the relation between units and the widely understood common good, including units engaged in economic activity, is their relation to more operational public goods. Therefore, starting from conclusions based on a probing research concerning Polish society’s attitude towards public goods (which is an index of public morality), we will try to prove that an oversimpli-fied and highly ideological understanding of economic freedom can lead to a) perception of market activities’ results in strictly economic categories, b) atrophy of priority values for each society such as the sense of responsi-bility and common good. Therefore the main thesis of the paper can be seen as the following state-ment: for each economic organization to perform correctly, it must be socially embedded in a defined axio-normative order. Economic order is a part of social order while freedom, as the leading objective idea, cannot be treated either in purely scientific or ideological categories.